PENGARUH STRATEGI PEMBELAJARAN MOBILE LEARNING DAN GAYA BELAJAR VISUAL TERHADAP PENGUASAAN KOSAKATA BAHASA JERMAN SISWA SMA NEGERI 1 MAROS - Agung Rinaldy Malik; Emzir Emzir; Sri Sumarni (Jurnal Visipena, 2020)
This research aims for knowing the impact toward the strategies of learning such as mobile learning and the mastery of visual learning toward the ability students about German vocabulary. This research is using quantitative and method of experiment with analysis Anava two lines. The sample of this research using random sampling as the result, it can be determined with two groups of sample at class XI SMA Negeri 1 Maros that are class XI IPA 1 as the class which used as experiment and XI IPA 2 as control class. The result of this research shows that there are the impact significantly toward the mastery of German language between the group of learning strategy mobile learning Lern Deutsch Goethe Institut and Instagram to the learning visual style of student. From this analysis it can be concluded that the value Qcount A1B-A2B = 4.33. From the table of Critical Value Q (Tukey) with α = 0.05, k = 4 and n = 11 Related to the value of Qtable (0.05; 4; 11) = 4.26. Because Qcount A1B-A2B = 4.33> Qtable = 4.26 or H0 is rejected, the mastery of the German language for groups of students who are given by the strategy of learning from Mobile Learning Lern Deutsch Goethe Institute and the student who has a learning visual style more higher (33,36) than the group of students who are given by the strategy of learning with Mobile learning Instagram (29.64) who has a learning visual style. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh strategi pembelajaran mobile learning dan gaya belajar visual terhadap penguasaan kosakata bahasa jerman siswa. Penelitian ini merupakan penelitian kuantitatif dengan metode eksperimen mengguanakan analisis Anava dua jalur. Sampel penelitian menggunakan random sampling sehingga dapat ditentukan dua kelompok sampel di Kelas XI SMA Negeri 1 Maros yaitu kelas XI IPA 1 sebagai kelas eksperimen dan XI IPA 2 sebagai kelas kontrol. Hasil penelitian ini menunjukkan: bahwa terdapat pengaruh yang signifikan pada penguasaan bahasa Jerman antara kelompok startegi pembelajaran mobile learning Lern Deutsch Goethe Institut dan Instagram terhadap gaya belajar visual siswa. Dari hasil analisis diketahui bahwa nilai Qhitung A1B-A2B = 4,33. Dari tabel Critical Values Of Q (Tukey) dengan α = 0,05, k = 4 dan n = 11 diketahui nilai Qtabel (0,05; 4; 11) = 4,26. Karena Qhitung A1B-A2B = 4,33 > Qtabel = 4,26 atau H0 ditolak, maka penguasaan bahasa Jerman kelompok siswa yang diberi strategi pembelajaran Mobile Learning Lern Deutsch Goethe Institut dan yang memiliki gaya belajar visual lebih tinggi (33,36) daripada kelompok siswa yang diberi strategi pembelajaran Mobile Learning Instagram (29,64) yang memiliki gaya belajar visual. Kata Kunci: strategi, pembelajaran, mobile learning, bahasa jerman